2011
DOI: 10.1021/ef200550m
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Detailed Kinetic Modeling Study of the Effect of Ozone on the Combustion of Methane

Abstract: New experimental results were obtained to better assess the effect of ozone on the burning velocity of premixed methane–air flames at atmospheric pressure and room temperature. Ozone was produced using a dielectric barrier discharge device, and its quantity was fixed equal to 5 g/Nm3 in air (2369 ppm of ozone). Measurements were performed using a Bunsen burner. Simultaneous to flame height measurements, a 1D Rayleigh scattering system was set up to investigate the impact of ozone on the thermal flame structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 19 publications
1
53
1
Order By: Relevance
“…Gao et al [32] showed that at higher pressures or at longer residence times, this is no longer the case, but at reduced pressures and the flow residence times in the current experiments, the reaction between the two is negligible. In addition, other works have noted that reactions between O 3 and saturated hydrocarbons such as CH 4 are quite slow at room temperature, and therefore the influence of O 3 on such fuels can be ignored [20]. Although the addition of reactions in the O 3 sub-mechanism does not consider synergistic effects, or how the addition of these reactions affects the rates of reactions present in the original mechanism, good agreement has been found between experimental results and the simulations [19,20,22].…”
Section: (B) Simulationsmentioning
confidence: 99%
“…Gao et al [32] showed that at higher pressures or at longer residence times, this is no longer the case, but at reduced pressures and the flow residence times in the current experiments, the reaction between the two is negligible. In addition, other works have noted that reactions between O 3 and saturated hydrocarbons such as CH 4 are quite slow at room temperature, and therefore the influence of O 3 on such fuels can be ignored [20]. Although the addition of reactions in the O 3 sub-mechanism does not consider synergistic effects, or how the addition of these reactions affects the rates of reactions present in the original mechanism, good agreement has been found between experimental results and the simulations [19,20,22].…”
Section: (B) Simulationsmentioning
confidence: 99%
“…The MSU mechanism [25,30] and the models of Starik and coworkers since 2001 [14,32] incorporate reaction OH + O 2 (1 ) = O + HO 2 (35) with the rate constant estimated in [14] without any explanation. It is tentatively retained in the present mechanism with high uncertainty factor since the calculated reverse rate constant of reaction (35) is 1-2 orders of magnitude smaller than the rate constant of reaction which, in its turn, is adopted from the model of Burke et al [54].…”
Section: Reactions Of Singlet Oxygenmentioning
confidence: 99%
“…It was demonstrated [34] that due to the incompleteness of the MSU mechanism (absence of many reverse reactions) it predicts an incorrect balance between O atoms, excited and ground state oxygen in ozone flames. It should be noted, however, that ozone reactions from the MSU mechanism [25,30] excluding excited oxygen species are mostly balanced, and their implementation in the recent studies of combustion enhancement by ozone [6,[35][36][37][38][39] is justified. Yet, conclusions based on the complete set of reactions taken from the MSU mechanism by Ombrello et al [7], and by Bourig et al [26], should be treated cautiously.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic scheme used is based on the kinetic scheme of Sarathy et al on the four butanol isomers [48], which also include ethanol and methanol reactions, in which an ozone sub-mechanism was implemented. This ozone submechanism was already used by Halter et al [49] to study the effect of ozone on primary reference fuels [46]. The final kinetic scheme is composed of 435 species and 2353 reactions, most of them reversible.…”
Section: Computationsmentioning
confidence: 99%